Earnings Quality and Financial Performance in State-Owned and Private Firms: A Comparative Analysis - Indra Lukmana Putra; Mochammmad Junus; Nurefa Maulana (TIJAB (The International Journal of Applied Business), 2026)
Background: The financial performance and earnings quality of pharmaceutical companies in Indonesia have become increasingly important given the sector’s expanding role in supporting national healthcare systems. Objective: This study aims to compare the earnings quality of state-owned and privately owned pharmaceutical companies listed on the Indonesian Stock Exchange (BEI) from 2019 to 2023, focusing on liquidity, profitability, solvency, and efficiency ratios. Method: Using secondary financial data, the study analyzes two state-owned and two privately owned pharmaceutical firms. Earnings quality is assessed through discretionary accruals and earnings persistence, while financial performance is evaluated using net profit margin, current ratio, debt-to-equity ratio, and total asset turnover. Descriptive statistical analysis is employed to compare performance across the two ownership groups. Results: The findings indicate that privately owned pharmaceutical companies outperform state-owned enterprises in key financial performance indicators, including net profit margin, current ratio, debt-to-equity ratio, and total asset turnover. In addition, privately owned firms demonstrate relatively stronger earnings quality, suggesting more stable and reliable financial reporting practices. Conclusion: The results highlight notable differences in financial performance and earnings quality between ownership structures in Indonesia’s pharmaceutical sector. These findings provide insights for policymakers, investors, and corporate managers seeking to improve financial transparency and operational efficiency within state-owned enterprises. Such improvements can contribute positively to the growth and development of Indonesia's pharmaceutical sector. Keywords: Financial Performances, Pharmaceutical Companies, Earnings quality